Application of EU Law by Serbian Courts - Stanivuković, Maja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In the Introduction, the author explains legal grounds for application of international and foreign law in judicial proceedings in Serbia. This is followed by a short passage on the manner of use of comparative law method in interpretation of domestic law. Thereafter, the main topic of this paper, the possible application of the European Union law by courts and other authorities in Serbia, comes to focus. At first, EU law is regarded as international law, i.e. law of an international organization, and then as foreign law, i.e. the law of a foreign country. The possibilities for application in these two forms are considered. The last chapter discusses the duties of Serbian courts to apply EU law arising from the Stabilization and Association Agreement, and the Interim Agreement. It is concluded that the proper intepretation of domestic provisions resulting from harmonization with the law of the European union requies systematic training of judges, both as to content of EU law and as regards the use of comparative law method in judicial practice.